Inventare insieme una crescita possibile Il Centro Tau: un'impresa educativa in un quartiere di Palermo - Schermi, Mario; DI GIOVANNI, Francesco (Scienze umane e Società, 2022)
The volume is the result of a choral enterprise, created on the sidelines of a choral experience. It tells, analyzes, and shares the social, pedagogical, civil, cultural and political experience of TAU Center, a community center funded in 1988 with the aim of offering concrete answers to growth needs of children, young people and adults in Zisa, a territory close to the historic center of the city of Palermo. The composition of the essays offers a mosaic and a fresco in whose attentive operators, far-sighted administrators, curious researchers and industrious citizens describe the waves of their paths along the paths of social planning, pedagogy of liberation and civil resistance. At TAU Center, Franciscan spirituality, Don Milani's school in Barbiana, Janusz Korczak's Warsaw ghetto, Paulo Freire's Brazil, Danilo Dolci's Partinico, resonated in an educational enterprise dedicated to the possibility of growing together, with care and patience, every day, thanks to the work of everyone around.